Penerapan “Nilai dan Etika” lingkungan menunjang penegakan hukum - Jumin, Hasan Basri (Universitas Islam Riau Indonesia, 2010)
Organism life’s created by God it has been several values. Human as a leader in earth (khalifah fil ardhi) must be has responsibility to implement its values with his ethics to care environments. The concept of relationship between ethics and development actually has already exist, however it has been almost extinguished. Environmental ethics are important to care an everlasting of environment for our live today and future. For protection of environment is necessary sense ethic and morality which it pay attention to environment. Pollution crisis’s like in sea, forest, atmosphere, lake, river, land and etc, it has resource from human behavior and human un-responsibility characters to view of nature and egoistic character. We needed to change our mind and our approach to nature become radical and controversial approach that it before we are thinking the nature is no meaning and human could be exploited as their like. Nature have a right to be respected not only for human life regarded to nature, but ontology obviously that human a integral part of the nature, and human as a member of ecology of community. Everyone must be having responsibility for respect to the nature right and respect to their live, growing, and development naturally. Implementation of that human creation, human must be have responsibilities to care, to protect, to make everlasting of nature and all of earth components. Application of values and ethics to environment they are assist the law enforcement, because that the human ethic and morality are very important to increase our life quality in earth.